(untitled) (Per Musi, 2024)
A multiple-case study was conducted within the context of the subject “Musical Practices and Fundamentals” of the Degree of Primary Education at the University of Seville. Five volunteers were subjected to an oral test in which they had to study four music sheets of two different difficulty levels, using two different means. The main objective of this study was to understand the differences between the perceptions of the participants toward the use of these two different means. The results show that the software had greater acceptance for those participants who had lower knowledge and skills regarding the musical content of the music sheets used in this study. Based on the results, it is understood that the introduction of this type of means could pose an improvement in the performance of the students, thereby reducing the differences in previous musical knowledge and skills, which, in turn, could enrich the methodology of the subject.